The Impact of Converting Cocoa Land to Rice Field on the Economic Welfare of Farmers in Katimbang Village, Matannga District, Polewali Mandar Regency - Jumardin; Dambe, Jumariani; Arfah, Ansar (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
This study aims to determine the impact of land conversion on farmers' income in Katimbang Village, Matangnga District, Polewali Mandar Regency. Agricultural land previously used for cocoa plants was converted into rice fields in response to the decline in cocoa agricultural yields due to pests and diseases, as well as low farmer income. This study uses a qualitative method with data collection techniques in the form of interviews, observations, and documentation. This method can provide in-depth understanding and easy-to-understand context. The study population consisted of 150 farmers who carried out land conversion, and 30 samples were taken. The results showed that farmers' income after land conversion increased significantly compared to before land conversion. Farmers who previously only received low incomes now receive higher incomes after converting land into rice fields. Land conversion has positive impacts, such as increasing employment and the economic quality of the community, although there are negative impacts such as increasing irrigation needs and reducing cocoa land. Therefore, it is important to consider the sustainability aspect in agricultural land management to support food security and farmer welfare.